Political motivations and electoral competition: Equilibrium analysis and experimental evidence - Michalis Drouvelis; Alejandro Saporiti; Nicolaas J. Vriend (Queen Mary University of London, School of Economics and Finance, 2011)
We study both theoretically and experimentally the complete set of Nash equilibria of a classical one-dimensional, majority rule election game with two candidates, who might be interested in power as well as in ideology, but not necessarily in the same way. Apart from obtaining the well known median voter result and the two-sided policy differentiation outcome, the paper uncovers the existence of two new equilibrium configurations, called 'one-sided' and 'probabilistic' policy differentiation, respectively. Our analysis shows how these equilibrium configurations depend on the relative interests in power (resp., ideology) and the uncertainty about voters' preferences. The theoretical predictions are supported by the data collected from a series of laboratory experiments, as we observe convergence to the Nash equilibrium values at the aggregate as well as the individual levels in all treatments, and the comparative statics effects across treatments are as predicted by the theory.
Keywords: C72; C90; D72; 330; electoral competition; power; ideology; uncertainty; Nash equilibrium; experimental evidence